Jual Beli Mata Uang Sistem Trading Forex dalam Perspektif Hukum Islam - Rahmat Rahmat; Sofyan Nur; Askar Patahuddin; Al Ikhsan Adil (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2021)
This research aims to find out and understand the laws of buying and selling currency online forex trading systems. The issues raised in this study are; First, how to buy and sell currency according to the Islamic view. Second, how to practice buying and selling currencies in an online forex trading system. Third, how to review Islamic law on the buying and selling of currencies in the forex trading system. The research method used is library research using normative and philosophical approaches and content analysis. The results of the study found that: First, buying and selling currencies in Islam is called currency exchange (al-Ṣarf), which is a type of muamalat allowed in Islam. Second, al-Ṣarf has several meanings that are almost the same, all indicating that the concept of exchange applies to the sale of two currencies in cash to each other even though the types are the same or different. Third, in the world of technology and communication in today's digital era, buying and selling currencies is often referred to as a forex trading system (foreign exchange), where the transaction model is divided into two ways, namely direct (offline) and indirect transactions (online). The law of offline forex trading is the law of disaster with two conditions, namely the handover directly in the assembly of the contract (should not be suspended) and if the type of currency is the same then it should not be overstated. However, the law of online forex trading is illegal because it leads to gambling, speculation, and buying and selling of garar, which can be seen from the transactions, types of goods, transaction actors, and systems that exist in online forex trading.